2014
DOI: 10.1002/gps.4082
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cognitive and affective dysfunction in patients suspected of mild cognitive impairment

Abstract: This sample of MCI patients demonstrated disturbances not only in memory but also in self-awareness and affect expression and perception on the BNIS. These dimensions should be included in the neuropsychological assessment of patients suspected of MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The BNIS is easy and fast to administer (13.8 minutes for neurological and psychiatric populations and 11.8 minutes for healthy participants, Prigatano et al, 2013). Furthermore, several studies (Boosman, Visser-Meily, Post, Duits, and van Heugten, 2013; Prigatano et al, 2014; Redfors et al, 2014) have shown that the BNIS is more sensitive than the MMSE in various neurological diseases (brain injury, stroke) that share characteristics with MS (e.g., slowing of processing speed). This screening tool might be of value in MS for the detection of both cognitive and behavioural disturbances and in helping to select patients for testing on the basis of a more complete cognitive and affective battery.…”
Section: Discussionmentioning
confidence: 99%
“…The BNIS is easy and fast to administer (13.8 minutes for neurological and psychiatric populations and 11.8 minutes for healthy participants, Prigatano et al, 2013). Furthermore, several studies (Boosman, Visser-Meily, Post, Duits, and van Heugten, 2013; Prigatano et al, 2014; Redfors et al, 2014) have shown that the BNIS is more sensitive than the MMSE in various neurological diseases (brain injury, stroke) that share characteristics with MS (e.g., slowing of processing speed). This screening tool might be of value in MS for the detection of both cognitive and behavioural disturbances and in helping to select patients for testing on the basis of a more complete cognitive and affective battery.…”
Section: Discussionmentioning
confidence: 99%
“…MCI is the transitional stage of cognitive function between normal aging and dementia. Although the cognitive function of people with MCI has not reached dementia, their core symptom, impaired memory, and complicated executive functions are significantly poorer than those of people with normal cognitive functions (Prigatano et al, 2014). Compared with people with normal cognitive functioning, every year approximately 10–15% of people with MCI will progress to dementia (Albert et al, 2011), and the chance of people with MCI progressing to dementia within one year is 10 times higher than those with normal cognitive functioning (Lopez‐Anton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%